Therapeutic approaches and outcomes in patients with larynx or hypopharynx high‐grade neuroendocrine carcinoma: A single‐center retrospective analysis. Issue 12 (15th September 2021) - Sousa, Luana Guimaraes; Lazar Neto, Felippe; Torman, Danice Karagiannis; Diaz, Eduardo M.; Rosenthal, David I.; Glisson, Bonnie S.; Bell, Diana; Ferrarotto, Renata
Abstract: Background: High‐grade neuroendocrine carcinoma of the larynx (HG‐NECL) is rare and aggressive with limited data regarding response to systemic therapy. We evaluated clinicopathological features, therapeutic approaches, and outcomes in patients with laryngeal or hypopharyngeal HG‐NECL. Methods: Data were retrospectively collected through 1997–2020. Median disease‐free (mDFS), progression‐free (mPFS), and overall survival (mOS) were estimated using the Kaplan–Meier method. Results: Fifteen patients were identified; most had locoregional ( N  = 7) or metastatic disease ( N  = 5). The main curative‐intent treatment was chemoradiation concurrent with platinum‐based chemotherapy; the rate of complete response was 78%. Most patients (80%) developed recurrence; the mDFS was 13.1 months. For the first‐line palliative therapy, the ORR and mPFS were 50% and 3.1 months, respectively. For all patients, the mOS was 17.8 months, and 8.6 months for metastatic disease. Conclusion: Laryngeal HG‐NEC is associated with high relapse rates and dismal prognosis for those with recurrent/metastatic disease. Novel therapeutic strategies are needed.